Classification of municipal solid waste based on Game Analysis. Issue 1 (March 2021) - She, Xiaoqing; Li, Xinghua; Mu, Tong; Shen, Shanshan
Abstract: With the increasing amount of garbage, every city gradually enforces the implementation of garbage classification. Aiming at the problem of garbage classification, a garbage classification implementation model based on the tripartite game among managers (government), producers (production enterprises) and consumers (residents) is constructed by using the method of dynamic game. Matlab is used to simulate and analyze the dynamic equation of tripartite replication, and find out the optimal strategy suitable for the three parties, then put forward measures to improve the way of waste classification, so as to reduce the amount of waste in a real sense and improve people's living standards.